Connecting sufficiency, materialism and the good life? Christian, Muslim and Hindu-based perspectives on EU-level - Klinkenborg, Hannah; Rossmoeller, Anica (Frontiers in Sustainability, 2022)
This article analyzes Christian, Muslim, and Hindu discourses and practices in relation to sufficiency, materialism, and the good life. The current political and scholarly debate emphasizes the need for a sustainability transformation and, more specifically, for reductions in resource use by the 'global consumer class. Within this discussion, the different approaches to and interpretations of the various facets of ecology and materialism, and the links between them, have become the primary focus. Questions about what a 'good life', as opposed to a consumerist lifestyle, means and the need to focus on sufficiency rather than efficiency are being (re-)considered. Given that religions and faith-based actors (FBAs) play an essential role as interpreters of norms and values in societies, especially when societies are facing particular challenges, it is important to understand how they communicate information about relevant ideas and actions. What do FBAs say about sustainable lifestyles, sufficiency, and the role of materialism vis-à-vis those two ideas? How do they relate it all to questions of faith? Do they use faith-based or secular idioms to address the ideas? How do FBAs relate the ideas to practices? To begin answering these questions, we here present a content analysis of relevant texts and supplement the finding thereof with an analysis of expert interviews. This article identifies and explores the role of faith-based ideas and practices in maneuvering towards one of the most substantial societal challenges in this period of late capitalism and its materialist dimension.